1982
DOI: 10.1093/ajcn/36.6.1234
|View full text |Cite
|
Sign up to set email alerts
|

Validity of telephoned diet recalls and records for assessment of individual food intake

Abstract: Six methods of assessing individual food intake reported by telephone were compared for accuracy. A sample of 107 students eating in a dormitory dining hall was used. Two 7-day and four 3-day diet records were reported by telephone to either an interviewer or an answering device; and fourteen 6-h recalls and seven 24-h recalls were obtained by an interviewer over the telephone. To examine validity, the investigators observed respondents' intake for 28 days. Food item agreement scores comparing observed and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
10

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(42 citation statements)
references
References 8 publications
1
31
0
10
Order By: Relevance
“…Mean total energy intake did differ, but this difference was entirely attributable to one interviewer. Several studies have concluded that telephone and faceto-face diet recalls appear to be interchangeable (Galasso et al, 1994;Tran et al, 2000;Casey et al, 1999;Krantzler et al, 1982). Fox et al (1992) reviewed telephone surveys as a method for obtaining dietary data and indicated that well designed and well administered telephone surveys are as good as, and may be better than, other dietary assessment methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean total energy intake did differ, but this difference was entirely attributable to one interviewer. Several studies have concluded that telephone and faceto-face diet recalls appear to be interchangeable (Galasso et al, 1994;Tran et al, 2000;Casey et al, 1999;Krantzler et al, 1982). Fox et al (1992) reviewed telephone surveys as a method for obtaining dietary data and indicated that well designed and well administered telephone surveys are as good as, and may be better than, other dietary assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of 24 h dietary recalls conducted by telephone is less than that of face-toface interviews (Derr et al, 1992), by as much as a factor of two (Weeks et al, 1983). Although most comparisons of 24 h dietary recalls conducted by telephone vs face-to-face interview have been performed using rather small samples (Galasso et al, 1994;Tran et al, 2000;Krantzler et al, 1982); Casey et al (1999) compared 700 telephone 24 h dietary recalls with 550 faceto-face interviews. This study concluded that 24 h dietary recalls conducted by telephone are a practical and valid tool for use in national food consumption surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation studies among adults have indicated that dietary recall information obtained by telephone was similar to information from energy intake for weight maintenance, 22 observation of congregate noon meal, 23 and tray cards with visual estimation in a college dining hall. 24 However, a validation study by Tran et al with adults indicated that although no significant differences were found in mean daily energy intake between inperson and telephone recalls, mean energy intake from both in-person and telephone recalls was significantly lower than total energy expenditure assessed using doubly labeled water. 21 In summary, among adults, information from dietary recalls is similar whether obtained in person or by telephone, although under-reporting is evident when compared to doubly labeled water.…”
Section: Introductionmentioning
confidence: 94%
“…The comparison of dietary recalls, records, and food frequency lists is one of the thorniest issues in the field of food habits measurement. Herbert Meiselman ran this study for Natick, working with Howard Schutz and Nora Krantzler of UC Davis and Nathan Macoby of Stanford University (Krantzler et al, 1982;Mullen, Krantzler, Grivetti, Schutz, & Meiselman, 1984).…”
Section: Research For Other Government Agenciesmentioning
confidence: 99%